A different perspective Asian and African leaders' views on missions - Brooking, Stuart M.; Overseas Council Australia (Sydney, NSW OCA, 2006)
Contents : Not what you'll hear at a missionary conference! -- Fate or call? -- The total approach of the Gospel -- Social factors influencing Christian corruption -- Mission in its long term perspective -- The context of ministry in South Africa: HIV/AIDS -- The good and bad a missionary brings -- The two hundred year goal -- Study guide. Includes biliographical references.
Donated by Overseas Council Australia, January 2007.
Keywords: Missions -- Asian Nationals' perspectives; Missions -- African Nationals' perspectives; Bible Colleges as missions